2016
DOI: 10.1080/13102818.2015.1130585
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of primary stability of single implants placed in fresh extraction sockets: a clinical trial

Abstract: Dental implants have been used for the last 20 years. With the latest modern developments, however, minimally invasive protocols and immediate implants are currently used. The aim of this study was to evaluate the primary stability of a new implant design. Thirty immediate implants were placed and they all achieved successful osseointegration. Primary stability was reached with all the implants after the first apical threads. Within the limitations of the present study, the immediate implant approach seems to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…advocated use of bovine inorganic bone substitute if the marginal gap was >2 mm. [ 9 ] However, Ferrus et al . concluded that this marginal gap eventually heals with formation of new bony tissue, thereby resolving the defect.…”
Section: Introductionmentioning
confidence: 99%
“…advocated use of bovine inorganic bone substitute if the marginal gap was >2 mm. [ 9 ] However, Ferrus et al . concluded that this marginal gap eventually heals with formation of new bony tissue, thereby resolving the defect.…”
Section: Introductionmentioning
confidence: 99%